Artificial intelligence-assisted phenotypic monitoring and diagnostic of wastewater microbiome management towards sustainability - Zijian Wang; Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Peisheng He; Annalisa Onnis-Hayden; Nicholas B. Tooker; Zijun Meng; Mark Wallace Miller; Kester McCullough; Stephanie Klaus; et al. (Water Research, 2026)

Screen-to-bench design of sulfur-coordinated Cr sites in ReS2 for selective ambient ammonia electrosynthesis - Xinghui Liu; Jia Sun; Nguyen Thi Phuong; Tran Ngoc Bao Thy; Xueyang Ji; Jingwen Liu; Han Jiang; Phung Thi Viet Bac; Sy Hieu Pham; Cuong Le Dinh; Thi Trung Chinh Nguyen; Dang Kim Hoang; et al. (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Recent duplications and rare structural variations revealed by comparative sequence analysis of low molecular weight glutenin subunits (LMW-GS) genes re-identified using LMWgsFinder in 26 genomes of the grass family - Shengli Zhang; Xiaojing Shan; Yun Wang; Tairui Lu; Daxing Xu; Han Gong; Yuchao Fan; Yuanyuan Guan; Junjie Zhao; Haili Sun; Dongfang Li; Haiyan Hu; et al. (Theoretical and Applied Genetics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Excitation functions for fast neutron induced reactions on Al, Zr, In and Au - B. Liu; G. Tian; R. Han; F. Shi; H. Sun; Z. Chen; Z. Zhang; Q. Li; P. Luo (Annals of Nuclear Energy, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P08-05 The Role and mechanism of O-GlcNAcylation in abnormalities of oocyte maturation and early embryonic development caused by PFOS exposure - Z. Wu; Q. Yuan; H. Qian; S. Han; Q. Xu; Y. Xia; Y. Fan; C. Lu (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Processable, reversible, and reusable 100 % bio-based pressure sensitive adhesives using nanostarch - Bong Soo Pi; Kyoungmun Lee; Chaeyeon Song; Byeongju Jeon; Youngkyu Han; Siyoung Q. Choi (Chemical Engineering Journal, 2024)

Sustainable regulation of calcium magnesium phosphate and rapeseed cake on soil-tea system in Mount Lushan, China - C. Han; Y. Ding; Z. J. Tang; Y. Q. Lai; M. Liu (Environmental Geochemistry and Health, 2024)

Antecedents in rural residents' acceptance of autonomous vehicles - Naihui Wang; Han Tang; Yi-Jia Wang; George Q. Huang (Transportation Research Part D: Transport and Environment, 2024)

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Arsenic-enhanced plant growth in As-hyperaccumulator Pteris vittata: Metabolomic investigations and molecular mechanisms - Yong-He Han; Yi-Xi Li; Xian Chen; Hong Zhang; Yong Zhang; Wei Li; Chen-Jing Liu; Yanshan Chen; Lena Q. Ma (Science of The Total Environment, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Paleocurrent and paleowind direction reconstruction research progress and perspectives: a review - F. Y. Zhao; C. L. Hu; C. C. Han; Y. Q. Dong; Q. X. Yuan (Australian Journal of Earth Sciences, 2023)

Rebound effect of carbon emissions of new energy vehicle consumption: a case study of Beijing - J. Zhou; W. Fang; X. Han; Q. Sun; D. Liu; S. Liu (International Journal of Environmental Science and Technology, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

Use of Moringa oleifera seeds powder as bio-coagulants for the surface water treatment - H. T. Nhut; N. T. Q. Hung; B. Q. Lap; L. T. N. Han; T. Q. Tri; N. H. K. Bang; N. T. Hiep; N. M. Ky (International Journal of Environmental Science and Technology, 2021)

Pseudomonas koreensis promotes tomato growth and shows potential to induce stress tolerance via auxin and polyphenol‐related pathways - Q. Guo; Y. Sun; M. Shi; X. Han; Y. Jing; Y. Li; H. Li; H. Lai (Plant and Soil, 2021)

Fatigue-Damage Evolution Characteristics of Interbeded Marble Subjected to Dynamic Uniaxial Cyclic Loads - Y. Wang; S. H. Gao; J. Q. Han (Geotechnical and Geological Engineering, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Geomechanical and Ultrasonic Characteristics of Black Shale During Triaxial Deformation Revealed Using Real-Time Ultrasonic Detection Dependence Upon Bedding Orientation and Confining Pressure - Y. Wang; J. Q. Han (Geotechnical and Geological Engineering, 2020)

Exploiting the reference genome sequence of hexaploid wheat: a proteomic study of flour proteins from the cultivar Chinese Spring - Susan B. Altenbach; Han-Chang Chang; Annamaria Simon-Buss; Toni Mohr; Naxin Huo; Yong Q. Gu (Functional & Integrative Genomics, 2020)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

Metabolites from the co-culture of nigranoic acid and Umbelopsis dimorpha SWUKD3.1410, an endophytic fungus from Kadsura angustifolia - L. Wang; D. Qin; K. Zhang; Q. Huang; S. Liu; M. J. Han; J. Y. Dong (Natural Product Research, 2017)

Response of plant functional traits to species origin and adaptive reproduction in weeds - J. H. Liu; X. H. Yong; Q. Han; A. Ali; Y. J. Wang (Plant Biosystems, 2017)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

Binding, fractionation, and distribution of Cs, Co, and Sr in a US coastal soil under saturated and field capacity moisture regimes - Leondra S. Lawson; Jacqueline Q. McComb; Ruipong Dong; Fengxiang X. Han; Christian Roger; Zikri Arslan; Hongtao Yu (Journal of Soils and Sediments, 2016)

Effect of a Rho Kinase Inhibitor on Cognitive Impairment Induced by Chronic Cerebral Hypoperfusion in Rats - Q. Zhang; J.-J. Zhang; Zh.-M. Han (Neurophysiology, 2015)

Bacterial Inactivation by Ultrasonic Waves: Role of Ionic Strength, Humic Acid, and Temperature - Gukhwa Hwang; Yosep Han; Siyoung Q. Choi; Sangho Cho; Hyunjung Kim (Water, Air, & Soil Pollution, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Identification of QTL for adult plant resistance to stripe rust in Chinese wheat landrace Caoxuan 5 - X. L. Zhou; Y. Zhang; Q. D. Zeng; X. M. Chen; D. J. Han; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Purification and characterization of a novel α-glucosidase from Malbranchea cinnamomea - Q. J. Yan; P. Han; S. Q. Yang; Z. Q. Jiang (Biotechnology Letters, 2015)

Sensitivity of Alternaria solani to boscalid and control of boscalid resistance with commonly-used fungicides in Shanxi, China - X. J. Shi; L. Ren; Y. Q. Song; J. C. Han; H. P. Liu; Y. J. Zhang (Australasian Plant Pathology, 2015)

Rapid Screening of Heavy Metals and Trace Elements in Environmental Samples Using Portable X-Ray Fluorescence Spectrometer, A Comparative Study - Jacqueline Q. McComb; Christian Rogers; Fengxiang X. Han; Paul B. Tchounwou (Water, Air, & Soil Pollution, 2014)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

Molecular mapping of a stripe rust resistance gene in wheat cultivar Wuhan 2 - X. L. Zhou; D. J. Han; H. L. Gou; Q. L. Wang; Q. D. Zeng; F. P. Yuan; G. M. Zhan; L. L. Huang; Z. S. Kang (Euphytica, 2014)
Stripe rust (or yellow rust), caused by Puccinia striiformis f. sp. tritici , is one of the most destructive diseases of wheat worldwide. Growing resistant cultivars is the best approach to control the disease. To identify and map genes for stripe rust resistance in wheat cultivar ‘Wuhan 2', an F 2 population was developed from a cross between the cultivar and susceptible cultivar Mingxian 169. The parents, 179 F 2 plants and their derived F 2:3 lines were evaluated for responses to Chinese races CYR30 and CYR31 of the pathogen in a greenhouse. A recessive gene for resistance was identified. DNA bulked segregant analysis was applied and resistance gene analog polymorphism (RGAP) and simple sequence repeat (SSR) techniques were used to identify molecular markers linked to the resistance gene. A genetic map consisting of five RGAP and six SSR markers was constructed. The recessive gene, designated Yrwh2 , was located on the short arm of chromosome 3B and flanked by SSR markers Xwmc540 and Xgwm566 at 5.9 and 10.0 cM, respectively. The chromosomal location of the resistance gene and its close marker suggest that the locus is different from previously reported stripe rust resistance genes Yr30 , QYr.ucw - 3BS , Yrns - B1 , YrRub and QYrex.wgp - 3BL previously mapped to chromosome 3B. Yrwh2 and its closely linked markers are potentially useful for developing stripe rust resistance wheat cultivars if used in combination with other genes.

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Effects of total replacement of dietary fish oil on growth performance and fatty acid compositions of hybrid tilapia (Oreochromis niloticus × O. aureus) - C.-Y. Han; Q.-M. Zheng; L.-N. Feng (Aquaculture International, 2013)

The C‐terminal cysteine of turbot Scophthalmus maximus translationally controlled tumour protein plays a key role in antioxidation and growth‐promoting functions - Z.‐X. Zhang; D.‐Y. Geng; Q. Han; S.‐D. Liang; H.‐R. Guo (Journal of Fish Biology, 2013)
The translationally controlled tumour protein (TCTP) of turbot Scophthalmus maximus ( SmTCTP ) contains only one cysteine (Cys 170 ) at the C‐terminal end. The biological role of this C‐terminal Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP was examined by site‐directed mutation of C170A (Cys 170 →Ala 170 ). It was found that C170A mutation not only obviously decreased the antioxidation capacity of the mutant‐ smtctp ‐transformed bacteria exposed to 0·22 mM hydrogen peroxide, but also significantly interrupted the normal growth and survival of the mutant‐ smtctp ‐transformed bacteria and flounder Paralichthys olivaceus gill ( FG ) cells, indicating a key role played by Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP . This study also suggested that the self‐dimerization or dimerization with other interacting proteins is critical to the growth‐promoting function of SmTCTP .

Choice of microsatellite markers for identifying homozygosity of mitotic gynogenetic diploids in Japanese flounder Paralichthys olivaceus - Y. X. Liu; H. Z. Han; Q. L. Wang; L. Jiang; S. L. Wang; X. Y. Zhang; Y. Liu; Y. F. Wang; Y. J. Liu; H. J. Liu (Journal of Fish Biology, 2013)
A set of 72 microsatellite markers distributed evenly among 24 linkage groups were selected from the published genetic linkage maps of Japanese flounder Paralichthys olivaceus . In two normal diploid full‐sib families, the test for Mendelian inheritance showed that genotypic segregation deviations were not significant at all analysed loci. To estimate microsatellite‐centromere map distances, four meiotic gynogenetic diploid lines were produced by the activation of eggs using UV irradiated sperm of red seabream Pagrus major and cold‐shock treatment to block the extrusion of the second polar body. Under the assumption of complete interference, 21 markers were located in the centromeric region, 39 in the telomeric region and the rest in the intermediate region of linkage groups. A total of 192 mitotic gynogenetic diploids from one spawn were identified by these markers. Genotype analysis showed that the number of homozygous individuals decreased as microsatellite‐centromere map distance increased on each linkage group.

Water Maze Spatial Learning Enhances Social Recognition Ability in Aged Rats - Q. Zeng; J. Han; B. Wang; Sh. An; Y. Duan; S. Dong; J. Ma; L. Yang; X. Cao (Neurophysiology, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Prolonged exclusive breastfeeding, autumn birth and increased gestational age are associated with lower risk of fever in children with hand, foot, and mouth disease - Q. Zhu; Y. Li; N. Li; Q. Han; Z. Liu; Z. Li; J. Qiu; G. Zhang; F. Li; N. Tian (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Prevalence and genetic characterization of respiratory syncytial virus (RSV) in hospitalized children in Korea - Yun Hee Baek; Eun Hye Choi; Min-Suk Song; Philippe Noriel Q. Pascua; Hyeok-il Kwon; Su-Jin Park; Jun Han Lee; Sung-Il Woo; Byung-Hoon Ahn; Heon-Seok Han; Yoon-Soo Hahn; Kyeong-Seob Shin; et al. (Archives of Virology, 2012)

Isolation, mapping, SNP detection and association with backfat traits of the porcine CTNNBL1 and DGAT2 genes - Q. Yin; H. -W. Yang; X. -L. Han; B. Fan; B. Liu (Molecular Biology Reports, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

A new total volume model of debris flows with intermittent surges: based on the observations at Jiangjia Valley, southwest China - N. Sh. Chen; Ch. L. Yang; W. Zhou; F. Q. Wei; Z. L. Li; D. Han; G. Sh. Hu (Natural Hazards, 2011)

Effect of paraquat on the antioxidative enzyme activities and lipid peroxidation in opium poppy (Papaver somniferum L.) - R. Zhao; P. -Y. Guo; X. -Y. Yuan; J. -Y. Wang; M. -Q. Han (Journal of Plant Diseases and Protection, 2010)

Active reassortment of H9 influenza viruses between wild birds and live-poultry markets in Korea - Ho Jin Moon; Min Suk Song; Deu John M. Cruz; Kuk Jin Park; Philippe Noriel Q. Pascua; Jun Han Lee; Yun Hee Baek; Dong Ho Choi; Young Ki Choi; Chul Joong Kim (Archives of Virology, 2010)

Application of an Improved Flow-Stress-Damage Model to the Criticality Assessment of Water Inrush in a Mine: a Case Study - H. Q. Zhang; Y. N. He; C. A. Tang; Bashir Ahmad; L. J. Han (Rock Mechanics and Rock Engineering, 2009)

Estimated PBDE and PBB Congeners in Soil from an Electronics Waste Disposal Site - H.-M. Wang; Y.-J. Yu; M. Han; S.-W. Yang; Q. li; Y. Yang (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Effects of brassinolide on the survival, growth and drought resistance of Robinia pseudoacacia seedlings under water-stress - K. R. Li; H. H. Wang; G. Han; Q. J. Wang; J. Fan (New Forests, 2008)

Ultrastructural and cytochemical studies on the infection process of Sclerotinia sclerotiorum in oilseed rape - L. Huang; H. Buchenauer; Q. Han; X. Zhang; Z. Kang (Journal of Plant Diseases and Protection, 2008)

Redirecting retroviral tropism by insertion of hepatitis B virus PreS1 core peptide into the envelope - P. Qi; J.-X. Han; Y.-Q. Lu; C.-X. Wang (Archives of Virology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spatial analysis for spring bloom and nutrient limitation in Xiangxi bay of three Gorges Reservoir - L. Ye; X. Q. Han; Y. Y. Xu; Q. H. Cai (Environmental Monitoring and Assessment, 2007)

Detection and identification of avian, duck, and goose reoviruses by RT-PCR: goose and duck reoviruses are part of the same genogroup in the genus Orthoreovirus - Y. Zhang; M. Liu; O. Shuidong; Q. L. Hu; D. C. Guo; H. Y. Chen; Z. Han (Archives of Virology, 2006)

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

Time Course Biochemical Responses of Green Algae Scenedesmus obliquus to Aluminum and Low pH - S. A. Jusu; F. X. Kong; B. Q. Qing; J. K. Tan; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Supply of Heat by Tsushima Warm Current in the East Sea (Japan Sea) - In-Seong Han; Yong-Q. Kang (Journal of Oceanography, 2003)

The complete nucleotide sequence of Beet black scorch virus (BBSV), a new member of the genus Necrovirus - Y. Cao; Z. Cai; Q. Ding; D. Li; C. Han; J. Yu; Y. Liu (Archives of Virology, 2002)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Enhanced salidroside production in liquid-cultivated compact callus aggregates of Rhodiola sachalinensis: manipulation of plant growth regulators and sucrose - J. F. Xu; P. Q. Ying; A. M. Han; Z. G. Su (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)